Pengujian Wagner's Law Versus Keynesian Hypothesis: Pendekatan Regional Indonesia - Pasaribu, Esti; Septriani, Septriani (Convergence: The Journal of Economic Development, 2021)
In this paper, we tested the Wagner’s Law against the Keynesian Hypothesis for Indonesia using granger causality test. After conducting theoretical and empirical theory, this paper is analysing the relationship between government expenditure and GDP percapita. The long run parameters and causality test found valid Wagners’ Law in Indonesia not Keynesian Hypothesis. The results reveal a positive and statistically significant long run effect running from economic growth toward the government expenditure refer to Wagner’s Law in Indonesia. Further more, the growth of population is giving a positive effect for government expenditure also.